2014
DOI: 10.1210/en.2013-1490
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Enriched Transcription Factor CREBH Interacts With Peroxisome Proliferator-Activated Receptor α to Regulate Metabolic Hormone FGF21

Abstract: Lipid metabolism is tightly regulated by nuclear receptors, transcription factors, and cellular enzymes. In this study, we demonstrated that the liver-enriched transcription factor CREBH (cAMP-responsive element binding protein, hepatocyte specific) and peroxisome proliferator-activated receptor α (PPARα) function as binary transcriptional activators to regulate lipid metabolism by activating fibroblast growth factor 21 (FGF21), a hepatic hormone that regulates whole-body energy homeostasis. Gain- and loss-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
153
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 29 publications
11
153
1
Order By: Relevance
“…In agreement with recent data (12), our results suggest that AHR can bind directly to the Fgf21 promoter at the same location to which the PPAR␣-RXR␣ and PPAR␣-CREBH heterodimers bind (7,8). Evidence implicates the PPAR␣-RXR␣ heterodimer in regulating lipid metabolism (19), whereas CREBH, independent of PPAR␣, induces a systemic inflammatory response upon ER stress (20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with recent data (12), our results suggest that AHR can bind directly to the Fgf21 promoter at the same location to which the PPAR␣-RXR␣ and PPAR␣-CREBH heterodimers bind (7,8). Evidence implicates the PPAR␣-RXR␣ heterodimer in regulating lipid metabolism (19), whereas CREBH, independent of PPAR␣, induces a systemic inflammatory response upon ER stress (20).…”
Section: Discussionsupporting
confidence: 92%
“…Utilizing EMSA, we show that the ChREBP-MLX complex does bind to the proximal Fgf21 ChoRE (Fig. 2B, lanes [5][6][7][8]. Also shown is ChREBP-MLX complex formation with a positive control oligonucleotide containing a consensus ChoRE (Fig.…”
Section: Crementioning
confidence: 83%
See 1 more Smart Citation
“…Several reports have indicated that FGF21 reduces the fasting plasma glucose, TG, insulin and glucagon levels in diabetic rhesus monkeys, indicating the potential for efficacy in humans 39,40) . Although FGF21 has been reported to be a direct PPAR target gene 41,42) , recent work indicates that CREBH 43) and HMGCS2 35) are also involved in the FGF21 gene expression. In this study, CREBH (Supplementary fatty acid -oxidative genes (ACSLs, CPT1A, CPT2, ACADVL, HADHA, HADHB, ACAA2) expression in human hepatocytes.…”
Section: K-877 Regulates the Gene Expression As A Spparmmentioning
confidence: 99%
“…FGF21 was initially described as a protein induced in the liver to control metabolic adaptation to long periods of starvation. This mRNA induction goes through the PPARa [13,73,74] and CREBH [75,76]. Later, several studies showed that FGF21 expression is regulated not only by fasting but also by other nutritional states [77].…”
Section: Fgf21 Expression Is Regulated By Nutrition Fasting and Feedingmentioning
confidence: 99%